INR Response to Low-Dose Vitamin K in Warfarin Patients. Issue 10 (October 2021) - Kulig, Caitlin E.; Roberts, A. Joshua; Rowe, A. Shaun; Kim, Hahyoon; Dager, William E.
Background: Literature suggests that 2 mg of vitamin K intravenously (IV) provides a similar effect as 10 mg to reverse warfarin. Doses <5 mg haven't been studied in depth. Objective: The objective was to determine the international normalized ratio (INR) reduction effect of ultra low-dose (ULD) IV vitamin K. Methods: This retrospective, observational cohort study compared IV vitamin K doses of 0.25-0.5 mg (ULD) versus 1-2 mg (standard low dose [SLD]). The primary outcome assessed ΔINR at 36 hours; secondary outcomes assessed ΔINR at 12 hours and 30-day venous thromboembolism (VTE) and mortality rates. Results: Of 88 patients identified (median baseline INR [IQR], 5.1 [3.1, 7.3] vs 4.5 [2.8, 8.2], ULD vs SLD, respectively), 59 had an INR at 12 hours. The ULD had fewer 12-hour INR values <2, with no statistical difference in the ΔINR at 12 hours between the ULD and SLD cohorts (median ΔINR, 2.2 [1.1, 3.4] vs 2.2 [1.1, 6.3]; P = 0.54; median INR, 2.3 vs 1.8). A total of 41 patients had both a 12- and 36-hour INR. No significant difference in the ΔINR between the 12- and 36-hour values occurred (median ΔINR, 0.52 [0.2, 0.91] vs ΔINR, 0.46 [0.18, 0.55]; P = 0.61), suggesting no rebound or excessive reversal and no difference in 30-day rates of VTE ( P > 0.99) or death ( P = 0.38). Conclusion and Relevance: ULD IV vitamin K reversed INR similarly to doses of 1-2 mg without rebound. A ULD strategy may be considered in patients requiring more cautious reversal.